2006
DOI: 10.1007/s11770-006-0017-0
|View full text |Cite
|
Sign up to set email alerts
|

Use of low-frequency signals to improve imaging quality under high-velocity basalt

Abstract: Wave equation wave field numerical modeling technology is applied to the observation that deep layer imaging is difficult below a screening layer of high-velocity basalt. Three simple high-velocity basalt models are designed on the basis of basalt formation characteristics. The analysis of deep-layer reflection seismic signal energy shows that lowfrequency seismic signals are capable of both penetrating the thin high-velocity basalt layer and reducing the diffraction noise caused by the rough surfaces. The sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…An Xueyong [9] and Zhao Jianzhang [10] put forward the suggestion of seismic acquisition survey parameters in view of the problems of the development of the surface layer and the superficial layer. She Deping [11] [12] using wave equation wave field numeric simulation technique, showed the low frequency signals having strong capacity both penetrating thin shielding high velocity basalt and reducing diffraction noises produced from rough surface, improving the imaging quality of deep beds below the shielding layer through using low frequency. Zhang Guangde [13] introduced geometry optimization using 3-D Gaussian beam forward modeling theory.…”
Section: Introductionmentioning
confidence: 99%
“…An Xueyong [9] and Zhao Jianzhang [10] put forward the suggestion of seismic acquisition survey parameters in view of the problems of the development of the surface layer and the superficial layer. She Deping [11] [12] using wave equation wave field numeric simulation technique, showed the low frequency signals having strong capacity both penetrating thin shielding high velocity basalt and reducing diffraction noises produced from rough surface, improving the imaging quality of deep beds below the shielding layer through using low frequency. Zhang Guangde [13] introduced geometry optimization using 3-D Gaussian beam forward modeling theory.…”
Section: Introductionmentioning
confidence: 99%
“…There are two main reasons why the use of low-frequency sources improves subbasalt reflection images: (1) the low frequencies generated by a seismic shot travel much further than high frequencies because basalts are often interbedded with thin layers of sediments and act as a low-pass filter (Mack, 1997;Ziolkowski et al, 2003;She et al, 2006;Lau et al, 2007), and (2) low frequencies are less sensitive to small heterogeneities (Fu, 2002(Fu, , 2003Ziolkowski et al, 2003). In Ziolkowski et al (2003), the effectiveness of low-frequency sources is demonstrated by comparing data acquired using low-frequency sources with conventional data acquired along the same line.…”
Section: Introductionmentioning
confidence: 99%